NEW PARADIGM IN PROVIDING PUBLIC SERVICES IN INDONESIA - Thamrin, Husni (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
Public service is one of the state’s obligations for the society. The society are entitled to receive public services as compensation for carrying out their obligations to the state. Public services are provided with the aim of creating society's welfare. Public services with a new model and paradigm are given by paying attention to the principle of justice, that is everyone who needs public services is given good and fair services according to the rights of service recipients. Public services must be provided in a non-discriminatory manner, it means that the recipient community is treated equally. The relationship between service providers and service recipients is inpersonal, which is relationships that are not based on the personal side and the public service providers or recipients.